Régimen de los procesos sobre estado civil en la ley de enjuiciamiento civil (con especial atención a los procesos sobre capacidad de las personas) - González García, Jesús María (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
Study on the regulation in the Spanish Law of Civil Procedure of 2000 about the general dispositions applicable to the processes on civil state, focussing in the processes relative to the declaration of incapacity, reintegration of the capacity and nonvoluntary entrance of the incapable one in appropiated health institutions.